Surviving, but not thriving: the politics of care and the experience of motherhood in academia. Issue 3 (3rd July 2019) - Low, Katharine; Damian Martin, Diana
ABSTRACT: This article considers the challenges of juggling the demands of motherhood in the experience of early career researchers operating in the British neoliberal academy, and discusses opportunities for alliance and resistance.